2021
DOI: 10.3390/jmse9080865
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Physical Modelling of Wave Overtopping on a Smooth Impermeable Dike with Promenade under Strong Incident Waves

Abstract: This paper presents a study of run-up/overtopping over a smooth impermeable dike with promenade using 2D and 3D mesh-based and mesh-free numerical models and results from 2D physical modelling for strong energetic incident waves. These waves induce plunging wave breaking and a complex water/air mixture turbulent flow before overtopped the dike, a challenging configuration for numerical models. The analysis is structured in two phases: (i) evaluates the results of 2D numerical and physical models for run-up and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The development of computational models for overtopping simulations progressed along with the advances in computing power. For example, some works analysed the wave-infrastructure interaction using 2D or 3D models to study overtopping [13][14][15]. Alternatively, other works use Machine Learning models to perform water flow estimations during overtopping [16] or predict overtopping events [17,18].…”
Section: Overtopping: Numerical Modellingmentioning
confidence: 99%
“…The development of computational models for overtopping simulations progressed along with the advances in computing power. For example, some works analysed the wave-infrastructure interaction using 2D or 3D models to study overtopping [13][14][15]. Alternatively, other works use Machine Learning models to perform water flow estimations during overtopping [16] or predict overtopping events [17,18].…”
Section: Overtopping: Numerical Modellingmentioning
confidence: 99%
“…These models use a series of differential equations in solving nonlinearity behaviour of seepage mechanism at specified boundary conditions. The accurate prediction of FOS is an indicator used for the stability of dike slope during water flow seepage [25].The validation of wave dissipation of slope breaches is highly required for obtaining run-up and overtopping over the structure [26]. However, a previous study on physical experimental tests and numerical models [27], demonstrated that the influence of some important geotechnical and hydraulic parameters on the development of matric suction, volumetric water content and slope stability remains unclear.…”
Section: Introductionmentioning
confidence: 99%